2007
DOI: 10.1212/01.wnl.0000265595.50915.1e
|View full text |Cite
|
Sign up to set email alerts
|

Polyarterial clustered recurrence of cervical artery dissection seems to be the rule

Abstract: More often than previously thought, the recurrence of spontaneous cervical artery dissection (sCAD) involves multiple cervical arteries in sequence. sCAD recurrence frequently appears to cluster within the first 2 months after the index event, rather than occurring steadily over time. The prognosis of recurring sCAD appears benign, particularly in patients already receiving antithrombotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 36 publications
(42 reference statements)
3
33
1
6
Order By: Relevance
“…MRI-identified recurrent dissections were asymptomatic in 8 of 9 patients (89%); the other patient had a stroke thought to be the result of hemodynamic failure. 236 Only a few factors have been reported to have an association with an increased risk of recurrence. In an additional report based on the Mayo Clinic cohort, 50% of CDs with a positive family history had recurrence compared with only 6% of those without a positive family history.…”
Section: Risk Of Dissection or Stroke Recurrencementioning
confidence: 99%
“…MRI-identified recurrent dissections were asymptomatic in 8 of 9 patients (89%); the other patient had a stroke thought to be the result of hemodynamic failure. 236 Only a few factors have been reported to have an association with an increased risk of recurrence. In an additional report based on the Mayo Clinic cohort, 50% of CDs with a positive family history had recurrence compared with only 6% of those without a positive family history.…”
Section: Risk Of Dissection or Stroke Recurrencementioning
confidence: 99%
“…All of these patients either had received heparin or had been anticoagulated orally with phenprocoumon, a regime that remained unchanged when the additional CAD occurred. In our study, we might have missed recurrences because of a shorter follow-up period, since Dittrich et al [22 ]reported recurrences in 3 patients at 1 week and in 3 other patients at 2 weeks. The relationship between AC and CAD recurrence needs to be confirmed by a longer follow-up period, beyond the first week.…”
Section: Discussionmentioning
confidence: 79%
“…Despite the unclear association between puerperium and arterial dissection, transient wall abnormalities induced by postpartum hormonal changes have been suggested as explanations [7] . Recurrence of dissection is rare and more frequent within the first 2 months after the initial event, reinforcing the possibility of a transient vascular disorder [8] .…”
Section: Discussionmentioning
confidence: 99%